2023
DOI: 10.3389/fnins.2023.1055445
|View full text |Cite
|
Sign up to set email alerts
|

The connection between heart rate variability (HRV), neurological health, and cognition: A literature review

Abstract: The heart and brain have bi-directional influences on each other, including autonomic regulation and hemodynamic connections. Heart rate variability (HRV) measures variation in beat-to-beat intervals. New findings about disorganized sinus rhythm (erratic rhythm, quantified as heart rate fragmentation, HRF) are discussed and suggest overestimation of autonomic activities in HRV changes, especially during aging or cardiovascular events. When excluding HRF, HRV is regulated via the central autonomic network (CAN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…Concerning the correlation between EEG and HRV parameters, previous studies have mainly focused on simultaneously recording EEG and HRV in response to cognitive tasks [ 138 140 ]. These studies indicated that executive function is closely related to vagally mediated HRV parameters as a result of the involvement of inhibitory inputs from the prefrontal-subcortical inhibitory circuits to the heart via the vagus nerve [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the correlation between EEG and HRV parameters, previous studies have mainly focused on simultaneously recording EEG and HRV in response to cognitive tasks [ 138 140 ]. These studies indicated that executive function is closely related to vagally mediated HRV parameters as a result of the involvement of inhibitory inputs from the prefrontal-subcortical inhibitory circuits to the heart via the vagus nerve [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…have all been shown to worsen due to a lowered HRV. Concussion frequency and severity can influence the development of these conditions, and although the degree of HRV decreases can differ based on factors such as the severity of a TBI, the negative impact that a lower HRV has on health remains the same whether it is caused by a TBI or some other neurological disease ( 33 ). Despite the authors writing that concussion is tied to ANS deficits, the other studies in this meta-analysis found no difference in values at rest and conclude that only in the presence of stressors will the ANS and HRV deficits become known ( 27 , 30 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of cross-sectional studies have shown there is an association between HRV and cognition, in generally healthy individuals across the age spectrum (for reviews, see [ 22 , 23 ]) as well as in subjects with neurocognitive disorders (for reviews see [ 23 , 24 , 25 , 26 ]) and with neuropsychiatric conditions (e.g., [ 27 , 28 , 29 , 30 ]). There are several possible explanations for this link.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, there has been an exponential rise in the number of publications on HRV and cognition [ 23 ]. Although the bulk of studies remain cross-sectional [ 22 , 47 ], longitudinal studies are beginning to emerge.…”
Section: Introductionmentioning
confidence: 99%